PD-L1/TLR7 dual-targeting nanobody-drug conjugate mediates potent tumor regression via elevating tumor immunogenicity in a host-expressed PD-L1 bias-dependent way - Wei Huang; Ji Zhou; Jia Li; Yakun Wan; Chao Hu; Meng Liu; Pan Xu; Feng Tang; Jianhua Sun; Xiaolu Yu; Yiru Long; Binfan Chen; et al. (Journal for ImmunoTherapy of Cancer)
Background Various tumors are insensitive to immune checkpoint blockade (ICB) therapy. Toll-like receptors (TLRs) establish the link between innate and adaptive immunity, which can assist T-cell activation and serve as promising targets for combination to enhance ICB therapy. Here, we aimed to improve efficacy for anti-programmed death ligand 1 (PD-L1) therapy by developing a PD-L1/TLR7 dual-targeting nanobody-drug conjugate (NDC), based on the PD-L1 nanobodies and TLR7 agonist we developed.Methods PD-L1 nanobodies were obtained by phage display screening and identified through T-cell activation bioassay, in vivo imaging and quantitative biodistribution study. Immune activation and PD-L1-inducing of TLR7 agonists were evaluated in diverse innate cell models. We constructed PD-L1/TLR7 dual-targeting NDCs by chemically coupling PD-L1 nanobodies and TLR7 agonists. The antitumor effect was evaluated via several murine or humanized solid tumor models. Immunophenotyping, immune cell depletion, tumor rechallenge, RNA sequencing and PD-L1-deficient models were combined to determine the mechanism for NDCs function. The dynamics of the in vivo behaviors of NDCs were assessed based on multiorgan changes in PD-L1 levels.Results The screened PD-L1 nanobodies were characterized as tumor-targeting and alleviated T-cell immunosuppression. The TLR7 agonists induced broad innate immune responses and intratumoral PD-L1 expression on antigen-presenting cells (APCs), and its antitumor effect was dependent on intratumoral delivery. The combination of TLR7 agonists and PD-L1 nanobodies activated both innate and adaptive immunity and upregulated PD-L1-related signaling pathways. After coupling to form dual-targeting NDCs, TLR7 agonists and PD-L1 nanobodies exerted synergistic antitumor effects and safety in either ‘hot’ or ‘cold’ tumor and early or advanced tumor models, reshaped the tumor immune microenvironment and induced antitumor immune memory. CD8+ T cells and natural killer cells were the main effector cells for NDCs to function. NDCs can promote PD-L1 expression on intratumoral APCs and tumor cells, and subsequently achieve targeted enrichment in tumors. Moreover, the efficacy of NDCs is biased toward dependence on host expression of PD-L1.Conclusions The novel PD-L1/TLR7 dual-targeting NDC exhibited potent efficacy against heterogeneous tumors through orchestrating innate and adaptive immunity, which could act as a promising strategy to improve ICB therapy and shows prospects for clinical development.